RANCANG BANGUN ALAT PEMANGGIL PETUGAS PEMADAM KEBAKARAN DENGAN MENGGUNAKAN METODE QFD DI WILAYAH DBAL - Fanny Gunawan Siregar; Basri Mustari; Dodik Pujiargo (Faculty of Science and Technology University of Pramita Indonesia, 2023)
- The Naval Base is one of the Main Commands for the development and operation of the Indonesian Navy. In order to be able to support all the tasks carried out by the Indonesian Navy, the base has responsibility for the implementation of the combat readiness and alertness of the elements of the Indonesian Warship (KRI) under it, which is part of the function of the base. Fire is a barrier factor for the base in its efforts to maintain the readiness and combat readiness of the KRI elements. PMK Lantamal Surabaya is a fire hazard management unit that has a working area at the Navy base. Currently there is no tool that is specifically provided to call firefighters in the area of the Naval base, the tool used to call firefighters today still utilizes a Central Telephone whose function is not only for fire emergencies but also for various uses, thus making firefighters slow to respond. In this study the authors tried to design a tool in the form of a Fire Extinguisher Calling Tool. With this fire extinguisher calling device, it can help firefighters respond more quickly to fire emergencies. This study uses the Quality Function Deployment (QFD) method. The QFD method is used to translate consumer needs and desires into product design characteristics. In this study, there were 2 (two) sources of Voice of Customer (VoC) data input, namely the implementing consumers were firefighters and consumer users were all Indonesian Navy soldiers. From the results of identifying consumer needs, solving existing contradictions is carried out by drafting and selecting concepts to obtain optimal results and produce several alternative product designs according to the standards desired by consumers.